Flocculation with heterogeneous composition in water environments: A review. (15th April 2022) - Ho, Que Nguyen; Fettweis, Michael; Spencer, Kate L.; Lee, Byung Joon
Highlights: The current findings of the heterogeneous composition of flocs are summarized. The effect of the composition of flocs on their structure and dynamics is reviewed. The interaction among heterogeneous components within flocs is explained. Human activities affecting the heterogeneous composition of flocs are also summarized. Abstract: Flocculation is a key process for controlling the fate and transport of suspended particulate matter (SPM) in water environments and has received considerable attention in the field of water science (e.g., oceanography, limnology, and hydrology), remaining an active area of research. The research on flocculation has been conducted to elucidate the SPM dynamics and to diagnose various environmental issues. The flocculation, sedimentation, and transportation of SPM are closely linked to the compositional and structural properties of flocs. In fact, flocs are highly heterogeneous in terms of composition. However, the lack of comprehensive research on floc composition and structure has led to misconceptions regarding the temporal and spatial dynamics of SPM. This review summarizes the current understanding of the heterogeneous composition of flocs (e.g., minerals, organic matter, metals, microplastic, engineered nanoparticles) and its effect on their structure and on their fate and transport within aquatic environments. Furthermore, the effects of human activities (e.g., pollutant discharge, construction) on floc composition are discussed. Graphical abstract: Graphical abstract Image, graphical abstract .